Exposiciones rábicas en Colombia: evaluación del sistema de vigilancia desde los actores (2015)
ABSTRACT: To identify the perception of the actors regarding the attributes of the rabies exposures surveillance system to generate any required recommendations. Methodology: Grounded theory was used up to the analysis of interpretive categories. The researchers used semi-structured interviews in the Colombian departments with the highest and lowest notified instances of rabies exposure. The interviewees were individuals with active roles (i.e. ranging from personnel in charge of notifying to system administrators). Finally, the topic of the interviews was the attributes taken into account by the Centers for Disease Control and Prevention. Results: fourteen descriptive categories emerged. These were related to nine attributes, surveillance, rabies and proposals for improvement. Of these, five analytical categories are considered resources for operation, experience, direct control of rabies and the role of actors in the process. The importance of the system in gathering information on public health was highlighted. Related publications are disregarded, and the participation of the actors in the planning process was perceived as low. The participants mentioned shortcomings related to the quality of the information, i.e. case classification, which affects its representativeness and sensitivity. Acceptability was associated with system tasks and the time spent in the process. Timeliness varies in the notification and adjustment processes. Conclusions: The perception of the attributes shows the articulation of the system concepts with the lessons learned by the actors. Some positive aspects are history and representativeness, while some of the negative traits are related to quality, sensitivity, usefulness and acceptability. Recommendations: to publish and improve participation in the system planning process.